I'm working on an assignment and I'm stuck on this proof. I feel like I'm on the right track but I can't find the way to prove the goal.
A ^ B
(A ^ ~C) --> ~D
A -> ~C
(B ^ E) --> (C v D)
I started by ^elim for A and B, then I started a subproof to start eliminating the conditionals, but how could I prove ~E when ~E is not in the premises? Only E is.
I imagined that I would have to eliminate the disjunction on the 4th premise and that I would be able to get to ~E on both of those subproofs but I can't find the logical way to do that. Any help would be appreciated -- Thanks